The dynamics of river confluences and their effects on the ecology of aquatic environment: A review - Yuan, Sai-yu; Xu, Lei; Tang, Hong-wu; Xiao, Yang; Gualtieri, Carlo (Journal of hydrodynamics. Series B, 2022)
Confluences act as critical nodes in a river system. They affect hydrodynamics, sediment transport, bed morphology, and eco-hydraulics of the river system. Convergence of streams produces the complex mechanism of flow momentum and mass mixing which may affect the aquatic environment locally and even lasting for a long distance downstream. The confluence creates a hotspot for the river system’s ecological change, which usually leads to changes in water temperature, suspended-sediment load, bed material, nutrient concentrations, water chemistry, and organic-matter content. Hence, the dynamics of river confluences are very complex and have critical effects on river system’s water environment and ecology. For this reason, a review summarizing turbulent flow, sediment transport, morphological-dynamics, mixing processes, and their effects on the ecology of the aquatic environment at river confluences is in order. A future research agenda and opportunities pertinent to river confluence are vitally emphasized as a multidisciplinary research topic.